2021
DOI: 10.1186/s13046-021-01837-6
|View full text |Cite
|
Sign up to set email alerts
|

NOX1 inhibition attenuates the development of a pro‐tumorigenic environment in experimental hepatocellular carcinoma

Abstract: Background The poor prognosis of advanced HCC and limited efficacy of current systemic treatments emphasize the need for new or combined targeted therapies. The development of HCC is a multistage process in which liver injury appears in a complex microenvironment associated with oxidative stress. NOX enzymes are the main source of ROS during hepatocarcinogenesis and NOX1 in particular has shown correlation with poor prognosis of HCC patients. This study evaluates the effect of pharmacological N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…DEN-injected wild-type (WT) mice that received a NOX1 inhibitor ML171 [ 174 ] developed fewer and smaller hepatic tumor nodules, compared to their vehicle-treated counterparts [ 38 ]. In agreement, a recent report indicated that pharmacological inhibition of NOX1 with GKT771 (Genkyotex) during HCC progression in mice attenuate the expression of several inflammatory markers, angiogenesis and fibrosis, therefore reducing the pro-tumorigenic environment [ 146 ]. Despite the opposite role of NOX1 and NOX4 in HCC (the first one promoting and the second one suppressing tumor progression), the fact that most of the liver tumor cells express low levels of NOX4 [ 115 ] facilitates the use of general NOX inhibitors as promising tools in the treatment of liver cancer.…”
Section: Nox Inhibitors As Therapeutic Tools In Liver Diseasessupporting
confidence: 66%
See 1 more Smart Citation
“…DEN-injected wild-type (WT) mice that received a NOX1 inhibitor ML171 [ 174 ] developed fewer and smaller hepatic tumor nodules, compared to their vehicle-treated counterparts [ 38 ]. In agreement, a recent report indicated that pharmacological inhibition of NOX1 with GKT771 (Genkyotex) during HCC progression in mice attenuate the expression of several inflammatory markers, angiogenesis and fibrosis, therefore reducing the pro-tumorigenic environment [ 146 ]. Despite the opposite role of NOX1 and NOX4 in HCC (the first one promoting and the second one suppressing tumor progression), the fact that most of the liver tumor cells express low levels of NOX4 [ 115 ] facilitates the use of general NOX inhibitors as promising tools in the treatment of liver cancer.…”
Section: Nox Inhibitors As Therapeutic Tools In Liver Diseasessupporting
confidence: 66%
“…Recent evidence indicates that NOX1 expression in macrophages mediates tumor promoting activity, through activating a ROS/MEK mechanism responsible of inflammatory cytokines production, thereby promoting the survival and proliferation of oncogene-carrying mutant hepatocytes, which ultimately accelerate HCC development [ 38 ]. Pharmacological inhibition of NOX1 with GKT771 during HCC progression in mice attenuates the expression of several inflammatory markers, angiogenesis and fibrosis, therefore reducing the pro-tumorigenic environment [ 146 ]. Besides NOX1, NOX2-derived ROS are also involved in TLR2-dependent M2 macrophage polarization, supporting tumor growth.…”
Section: Role Of Noxs In Hccmentioning
confidence: 99%
“…On the contrary, NOX1 mediates autocrine growth and survival of liver tumor cells and anti‐apoptotic signals induced by TGF‐β through the transactivation of the EGF receptor pathway 32,33. Indeed, NOX1 pharmacological inhibition impairs cell growth and enhances TGF‐β‐induced apoptosis,34 and attenuates the development of a pro‐tumorigenic environment in experimental HCC 35. Overall, NOX1 and NOX4 exert opposite roles in the control of liver growth and apoptosis, and their balance may dictate cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor microenvironments are characterized as hypoxia and energy deficiency, which render cancer cells and other stromal cells to go through metabolic reprogramming ( 99 ), so as to meet their needs for increasing biological process of bioenergy, biosynthesis, and redox balance ( 100 ). The activation of CAFs in HCC also requires a large quantity of energy to promote cell proliferation, ECM and cytokine release, and the migration toward certain pro-fibrotic and pro-inflammatory regions ( 101 ). As a consequence, metabolic reprogramming and energy expenditure regulation play key roles in the function change of CAFs during the HCC microenvironment and liver injury.…”
Section: The Metabolic Reprogramming Of Cafs In Hcc Progressionmentioning
confidence: 99%